The Influence Of Transformational Leadership Style And Organizational Culture On Employee Performance At The Medan State Administrative Court - Riri Andriani Rangkuti; Ahmad Aswan Waruwu; Muhammad Yalzamul Insan (Utan Kayu Publishing, 2025)
This research aims to determine the influence of Leadership Style and the Organizational Culture on Employee Performance at Asahan University. This research uses quantitative research and was conducted at the Medan Administrative District Court. Sample used was 60 employees. The data collection technique used was distributing questionnaires, the research model used was path analysis and the measuring tool used SmartPLS version 4.0. The research results are as follows: Leadership Styles has a positive and significant effect on Employee Performance at Medan Administrative District Court with an original sample value of 0.528, a statistical T value of 6.663 and a P value of 0.000. The Organizational Culture has a positive and insignificant effect on employee performance at the Medan Administrative District Court with an original sample value of -0.107, a statistical T value of 1.239 and a P value of 0.215.